Changes in Nonverbal Communication in Public Communication Before and During the COVID-19 Pandemic: Literature Review of Scientific Papers for the 2014-2022 Period - Angela Audrey Sutanto; Astri Yogatama; Liliana .; Hans Juwiantho (Ultimacomm: Jurnal Ilmu Komunikasi, 2022)
Nonverbal communication is all messages or all communication cues that are not words or do not use words. The COVID-19 pandemic, has changed aspects of non-verbal communication, especially in gestures, paralinguistics, and microexpression in the context of public communication. This research aims to find the differences in nonverbal communication, gestures, paralinguistics, and microexpression before and during the COVID-19 pandemic. The data are from 30 journals with the central theme of non-verbal communication in the context of public communication and containing specific classifications of gestures, paralinguistics, and microexpressions. This research uses the quantitative-descriptive content analysis method with. Meanwhile, the theory used in this study is the theory of J. Schneider, D. Börner, P. van Rosmalen & M. Specht (2017) and Vanessa Van Edwards' characteristics of microexpression (2013). Thus the aspects of nonverbal communication that have changed the most from before and during the COVID-19 pandemic are gestures (upright and calm body position) and paralinguistics (tempo), meanwhile microexpession did not experience significant changes.